2023
DOI: 10.3389/fpls.2023.1302046
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of stem cell activity in plant development and stress responses

Huankai Zhang,
Yangwei Mu,
Hui Zhang
et al.

Abstract: Stem cells residing in plant apical meristems play an important role during postembryonic development. These stem cells are the wellspring from which tissues and organs of the plant emerge. The shoot apical meristem (SAM) governs the aboveground portions of a plant, while the root apical meristem (RAM) orchestrates the subterranean root system. In their sessile existence, plants are inextricably bound to their environment and must adapt to various abiotic stresses, including osmotic stress, drought, temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 228 publications
0
4
0
Order By: Relevance
“…Genetics and bulk gene expression approaches have identified and localized some of these regulators (Kitagawa and Jackson, 2019; Lindsay et al, 2024). This has led to the identification of specific cell types and domains, including the central zone which harbors stem cells, the organizing center which specifies the stem cells, and the peripheral zone which initiates lateral organ primordia (Fuchs and Lohmann, 2020; Hong and Fletcher, 2023; Karami et al, 2023; Uchida and Torii, 2019; Wang et al, 2020; Zhang et al, 2023). These cell types and developmental domains are highly conserved in both vegetative and inflorescence shoot meristems, and across different plant species (Greb and Lohmann, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Genetics and bulk gene expression approaches have identified and localized some of these regulators (Kitagawa and Jackson, 2019; Lindsay et al, 2024). This has led to the identification of specific cell types and domains, including the central zone which harbors stem cells, the organizing center which specifies the stem cells, and the peripheral zone which initiates lateral organ primordia (Fuchs and Lohmann, 2020; Hong and Fletcher, 2023; Karami et al, 2023; Uchida and Torii, 2019; Wang et al, 2020; Zhang et al, 2023). These cell types and developmental domains are highly conserved in both vegetative and inflorescence shoot meristems, and across different plant species (Greb and Lohmann, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…RAM organization has evolved to become highly plastic and dynamic in response to environmental triggers, such as water and nutrient availability [9,10]. Under stress conditions, the RAM is rapidly reorganized, and the root growth is enhanced, thus providing effective strategies to cope with the stresses [9][10][11]. This environment-responsive developmental plasticity is linked to reactive oxygen species (ROS) and nitric oxide (NO), which act as signals specifically to regulate RAM function, connecting with hormones [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…•− and H 2 O 2 regulates the transition of root systems between proliferation and differentiation [22]. Recent advances indicate that H 2 O 2 functions as a signaling molecule to control RAM size and SCN maintenance by regulating the factors of auxin, PLTs, SCR, and SHR [11,[23][24][25]. In this review, we focus on summarizing the key factors in the regulation of RAM activity and discuss the signaling transduction of H 2 O 2 in the maintenance of RAM activity.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of these root types is characterized by temporal and spatial developmental variability, implying that they have specific functions during maize development ( de Dorlodot et al, 2007 ). At the early seedling stage, roots and mesocotyls can respond sensitively to phytohormones and environmental stresses, and they are important organs as evaluators of stress tolerance ( Niu et al, 2020 ; Zhang et al, 2023 ). Previous studies have shown that FHY3/FAR1 genes participate in response to drought stress, but their functions in maize are still unknown.…”
Section: Introductionmentioning
confidence: 99%